Plant cell culture as emerging technology for production of active cosmetic ingredients. Issue 11 (15th July 2018) - Georgiev, Vasil; Slavov, Anton; Vasileva, Ivelina; Pavlov, Atanas
Abstract: Plants have always been the main source for active cosmetic ingredients, having proven health beneficial effects on human, such as anti‐aging, antioxidant, anti‐inflammatory, UV‐protective, anti‐cancer, anti‐wrinkle, skin soothing, whitening, moisturizing, etc. Extracts from herbal, aromatic and/or medicinal plants have been widely used as effective active ingredients in cosmeceuticals or nutricosmetics, especially in products for topical application and skin‐care formulations. However, over the past decade, there has been an increasing interest to plant cell culture – derived active cosmetic ingredients. These are "new generation" of high quality natural products, produced by the modern plan biotechnology methods, which usually showed stronger activities than the plant extracts obtained by the classical methods. In this review, the advantages and the current progress in plant cell culture technology for the production of active cosmetic ingredients have been summarized, and discussed in details within a presented case study for calendula stem cell product development.